2017
DOI: 10.1007/s00520-017-3687-7
|View full text |Cite
|
Sign up to set email alerts
|

Screening for symptom burden and supportive needs of patients with glioblastoma and brain metastases and their caregivers in relation to their use of specialized palliative care

Abstract: Symptom burden and supportive needs were high, but even more caregivers than patients expressed high distress and supportive needs. SPC appears to reach the target group, both patients and caregivers with elevated symptom burden. Targeted interventions are needed to improve tiredness and drowsiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…In seven studies describing symptoms in the treatment phase, symptoms were registered according to the CTCAE (Common Terminology Criteria for Adverse Events), varying from registering all grades, to only registering grade 3 and 4 [25, 28, 3135]. In four studies data were collected by means of validated PROMs including symptoms: the EORTC module for brain cancer patients (EORTC QLQ-BN20) [27], the ESAS-r (ESAS revised) [30], the Hospital Anxiety and Depression Scale (HADS) [26, 36], the Fatigue Severity Scale (FSS) [36], and the Epworth Sleepiness Scale (ESS) [36]. Telephone interviews with patients were performed in the study of Sizoo, including 58 patients, in addition to data that were obtained from the medical records [37].…”
Section: Resultsmentioning
confidence: 99%
“…In seven studies describing symptoms in the treatment phase, symptoms were registered according to the CTCAE (Common Terminology Criteria for Adverse Events), varying from registering all grades, to only registering grade 3 and 4 [25, 28, 3135]. In four studies data were collected by means of validated PROMs including symptoms: the EORTC module for brain cancer patients (EORTC QLQ-BN20) [27], the ESAS-r (ESAS revised) [30], the Hospital Anxiety and Depression Scale (HADS) [26, 36], the Fatigue Severity Scale (FSS) [36], and the Epworth Sleepiness Scale (ESS) [36]. Telephone interviews with patients were performed in the study of Sizoo, including 58 patients, in addition to data that were obtained from the medical records [37].…”
Section: Resultsmentioning
confidence: 99%
“…When patients are on chemotherapy, neuro-oncologists should take into account that mostly caregivers organize the family life, take care of the patients and are in charge when patients suffer from side effects. In order to relieve caregivers, early integration of palliative care, outpatient services, social services and interdisciplinary treatment (during ongoing tumor-specific therapies) are required ( 44 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specific indications for specialty palliative care in HGG are less clearly defined [ 13 ]. Few studies have been published specifically addressing the role of specialty palliative care in this unique population, and no randomized, controlled trials have yet been conducted [ 60 , 72 ]. In one observational study of 50 patients with glioblastoma admitted to a tertiary hospital in Australia who had contact with specialty palliative care during that admission, the most common reason for palliative care consultation was “complex discharge planning” (78%), followed by request from a community palliative care service (40%) or symptom management (28%) [ 72 ].…”
Section: Approachmentioning
confidence: 99%
“…These findings are consistent with another qualitative study in which HGG patients reported feeling that health care professionals were not open to talking about the future and were uncomfortable talking about palliative care, which the patients felt was a barrier in their relationships with those providers [ 62 ]. In an observational study of 79 patients with glioblastoma (54 patients; 68%) or brain metastases (25 patients; 32%) who were offered palliative care consultation within 2 months of diagnosis (or diagnosis of relapse), 38% opted to pursue the consultation [ 60 ]. Educating providers about appropriate ways to introduce palliative care may help to allay patient fears, and focusing on primary palliative care interventions or integrated models of care may be optimal in reducing appointment burden.…”
Section: Approachmentioning
confidence: 99%